A study of the effects of foundation uplift on the seismic loading of wind turbine tower and shallow foundation using a new dynamic Winkler model. (15th September 2020) - Wang, Lilin; Ishihara, Takeshi
Highlights: QzSimple4 is proposed using PySimple3 for compression and gap in QzSimple1 for founation uplift. QzSimple4 agreees well with experiments but QzSimple2 does not. Foundation uplift significantly increases moments of shallow foundation resting on stiff soil. Abstract: In this study, the effects of foundation uplift on the seismic loading of wind turbine tower and shallow foundation are investigated. A dynamic Winkler model is proposed for the dynamic response analysis of shallow foundation supported structures and is named as QzSimple4, in which PySimple3 is applied to replace the elastoplastic component in QzSimple2 for the compression under the foundation and the gap model in QzSimple1 is assembled to capture the foundation uplift. The proposed model agrees well with the q-z experimental backbone curves and reasonably captures the acceleration responses of the bridge deck and the settlement-rotation responses of the shallow foundation under various excitation levels. However, QzSimple2 model strongly overestimates the q-z backbone curves in terms of linear range and ultimate bearing capacity, which leads to obviously overestimate some acceleration responses of the bridge deck and significantly underestimate the settlement responses of the shallow foundation. Finally, a systematical study is performed to investigate the effects of foundation uplift on the seismic loading by using the proposed Winkler model and the equivalent linear sway-rocking model. The foundation uplift occurs under severe earthquakes. Without considering the foundation uplift, the moment on the wind turbine tower is slightly overestimated, while that on the shallow foundation is significantly underestimated for the large soil stiffness. This is one reason why the shallow foundations at Aso-Nishihara wind farm were damaged during the Kumamoto earthquake.